The lying club [large type] - Ward, Annie, 1970- (Thorndike Press large print core series., 2022)
"At an elite private school nestled in the Colorado mountains, Natalie, an office assistant, dreams of having a life like the school moms she deals with every day. Women like Brooke--a gorgeous heiress, ferociously loving mother and serial cheater--and Asha, an overprotective mom who suspects her husband of having an affair. Their fates are bound by the handsome assistant athletic director Nicholas, whom Natalie loves, Brooke wants and Asha needs. But when two bodies are carried out of the school one morning, it seems the tension between mothers and daughters, rival lovers, and the haves and have-nots has shattered the surface of this isolated, affluent town--where people stop at nothing to get what they want."--Provided by publisher.